Professional identity of students in the learning process at the university - Shenne Mainy, Chochagai Mongush, Olga Mongush,; Anna Frokol, Choduraa Mongush,; Sendazhi, Saylan (Opción, 2019)
The topic of the article is relevant in connection with the requirement to rationally correlate in modern socio-economic conditions the goals and objectives of the psychology of vocational education in universities with the situation of the labor market. Reliability creates the differences in the components of motivation of professional self-determination by sex and checks them by methods of analytical mathematical statistics including the method of establishing the validity of differences, U-Mann-Whitney test, and regression analysis and reveal the significance of the influence of objective factors on the studied variables and correlation analysis. A computer program «SPSS-17» was used to process empirical data.